Survey on the Finnsh biotechnology industry: Background and descriptive statistics - Raine Hermans; Martti Kulvik; Antti-Jussi Tahvanainen (The Research Institute of the Finnish Economy (ETLA), 2005)
ETLA, the Research Institute of the Finnish Economy, conducted surveys at the end of 2004 and at the beginning of 2002 on the enterprises listed in the Index of Biotechnology Companies in the Finnish Bioindustries organization. The surveys provide data on financial accounting, R&D activities, intellectual property rights, and sales forecasts. In addition to the updates, the ETLA 2004 Survey also provides detailed linkages to product-level information that incorporates R&D- and sales figures, forecasts thereof, collaboration patterns, science-base mapping, and academic origin of the innovations. This also paper presents descriptive statistics on intellectual capital and value creation of the biotechnology industry. Finally, we discuss the main findings of the survey and indicate topics for further research.
Keywords: 330; Biotechnische Industrie; Unternehmensfinanzierung; Forschungssubvention; Forschungsfinanzierung; Public-Private Partnership; Finnland